Nurturing Potential: Unveiling the Psychological Landscape of Care and Education for Children with Special Needs - Zamzam, Rohimi; Suharsiwi, Suharsiwi; Susilahati, Susilahati; Ni'matuzahroh , Ni'matuzahroh (International Conferences on Early Childhood Education Proceedings, 2025)
The focus of this research is on the important role of psychology in shaping the care and education of children with special needs. In parenting, family psychology and the personality of children with special needs prove themselves to be critical elements in creating a positive environment. On the educational side, developmental psychology for children with special needs guides educators in designing appropriate learning approaches, while inclusive education, with a focus on inclusive psychology, increases the accessibility and success of learning. Psychological challenges, such as stigma and emotional stress, faced by parents and educators are also highlighted. Psychological strategies such as counselling, group support, and training have proven effective in overcoming these challenges. In conclusion, this article highlights the importance of integrating psychology in the context of care and education of children with special needs to create an inclusive environment that supports the optimal development of these children